(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Adiantum capillus-veneris Linn. of Adiantaceae family is one of most common plants that have found diverse medicinal uses in the indigenous systems of medicine. It has been used in cold, skin diseases, bronchitis, hair fall and inflammatory diseases. It is also considered as tonic and diuretic. The previous studies showed that Adiantum capillus veneris contained many secondary metabolites and exerted antimicrobial, antiinflammatory, analgesic, hypoglycemic, antioxidant, antiproliferative, antidermatitis, neuroprotective, anticholesterolemic and many other effects. The present review will highlight the chemical constituents and the pharmacological and therapeutic effects of Adiantum capillus veneris. A wide range of chemical compounds including adiantone, diplopterol, kaempferol, naringin, neoxanthin, populnin, quinic acid, rhodoxanthin, rutin, shikimic acid, zeaxanthin etc. have been isolated from this plant. The plant leaves and stem of Adiantum capillus veneris L. were found to contain higher amount of triterpenoids and flavonoids. Adiantum capillus-veneris L., is nowadays gaining interest by the scientific researchers due to its folklorics and because of its therapeutic value, easy availability and degree of research work which is not done. The present review aims at reviewing the research works undertaken till date, on this plant in order to provide sufficient baseline information for future works and for commercial exploitation. The opening of a wide venue for further research and translation into clinical settings is also envisaged.